2020
DOI: 10.1038/s42255-019-0158-0
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin secretion by Na+-dependent Ca2+-induced Ca2+ release in pancreatic delta cells

Abstract: Pancreatic islets are complex micro-organs consisting of at least three different cell types: glucagon-secreting α-, insulin-producing βand somatostatin-releasing δ-cells 1. Somatostatin is a powerful paracrine inhibitor of insulin and glucagon secretion 2. In diabetes, increased somatostatinergic signalling leads to defective counter-regulatory glucagon secretion 3. This Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, subject a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 34 publications
(50 reference statements)
4
40
1
Order By: Relevance
“…A recent study suggested that delta-cell [Ca 2+ ] i oscillatory activity is reduced after HFD feeding [49], in keeping with the reduction of somatostatin secretion we observe. We note that the effects of HFD on somatostatin secretion – when mice remain largely normoglycaemic – are different from those observed once hyperglycaemia has developed [50]. Not only was somatostatin secretion reduced in HFD mice, their alpha-cells were also much less sensitive to SST in the present study, with Ca 2+ oscillation frequency persisting in HFD islet when exposed to SST.…”
Section: Discussioncontrasting
confidence: 64%
“…A recent study suggested that delta-cell [Ca 2+ ] i oscillatory activity is reduced after HFD feeding [49], in keeping with the reduction of somatostatin secretion we observe. We note that the effects of HFD on somatostatin secretion – when mice remain largely normoglycaemic – are different from those observed once hyperglycaemia has developed [50]. Not only was somatostatin secretion reduced in HFD mice, their alpha-cells were also much less sensitive to SST in the present study, with Ca 2+ oscillation frequency persisting in HFD islet when exposed to SST.…”
Section: Discussioncontrasting
confidence: 64%
“…Earlier work in rat islets showed that DA inhibits SST secretion via its actions on D 2 -like receptors 92 . This raises the possibility that the DA synthesized by αand β-cells also locally activates δ-cell D2R to inhibit SST secretion and thus removes SSTmediated inhibition of insulin and glucagon release 32,91,[93][94][95][96][97][98] . Such paracrine DA signaling that involves α-, β-, and δ-cells may offer an additional dimension to our understanding of the intra-islet regulation of hormone secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the somatostatin receptor (SSTR) antagonist CYN154806 restores glucagon secretion at 1 m m glucose in diabetic mice and in some islet preparations from donors with T2D (Vergari et al . 2020). In such patients, blocking the K ATP channel component, low‐dose SUs might lower the resting K + conductance sufficiently to stimulate secretion at 1 m m glucose but it would not correct the suppression due to inhibition of exocytosis.…”
Section: Islet Katp Channels and Diabetes: Pathophysiological And Thementioning
confidence: 99%
“…5E). Indeed, T2D is associated with hypersecretion of somatostatin at low glucose (Vergari et al 2020). Somatostatin inhibits glucagon secretion by several mechanisms including the activation of G protein-coupled inward-rectifying K + channels (GIRK) and a direct effect on exocytosis (Rorsman & Huising, 2018).…”
Section: Effects Of Tolbutamide and Diazoxide On Glucagon Secretionmentioning
confidence: 99%
See 1 more Smart Citation